Urgensi Pendaftaran Warna sebagai Potensi Merek Dagang Berdasarkan Undang-undang Nomor 20 Tahun 2016 - Vanny Fiandra Cahyani; Laina Rafianti (Pusat Riset dan Inovasi Nasional, 2024)
The use of a mark serves not only as a distinguishing factor for a company but also as a strategic tool for marketing and advertising. Color, as a crucial element in brand identity, has the ability to convey messages, influence consumer perceptions, and enhance brand value. Therefore, it is not uncommon for companies to seek protection for colors as trademarks to ensure a definite level of safeguarding. In Law Number 20 of 2016 concerning Trademarks and Geographical Indications in Indonesia, the registration of color is not explicitly recognized as a trademark that can be registered, but it is also not prohibited. The findings of this research indicate the importance of Indonesian law in allowing the registration of color as a trademark, considering that color has a strong identification power for consumers, and many companies have successfully created associations between colors and their marks through consistent usage.